Cathedral, Trinidad - (:unkn) unknown (My University, 2008)
Photo of the Holy Trinity Cathedral, an Anglican church in Port of Spain, Trinidad.
Colour: Brown and White; Style: Portrait; Other: Bordered; Undivided
Keywords: Postcards; Church buildings--Trinidad and Tobago; Cathedrals--Trinidad and Tobago; Trinidad and Tobago; Church architecture--Trinidad and Tobago; Holy Trinity Cathedral